Follicular Lymphoma Manifesting as an Isolated Colorectal Polyp‐Like Morphology - Yasuhiko Hamada; Yuhei Umeda; Hayato Nakagawa (JGH Open)
ABSTRACT Background Primary gastrointestinal (GI) follicular lymphoma (FL) is a rare entity, and colorectal FL presenting as a solitary polyp is particularly uncommon. Case Presentation A 60‐year‐old woman presented with hematochezia. Colonoscopy incidentally identified an 8‐mm polyp in the transverse colon, which was subsequently removed via cold snare polypectomy. Histopathological examination confirmed Grade 1 FL, with immunohistochemical analysis revealing positivity for CD10, CD20, and Bcl‐2. Further diagnostic evaluation demonstrated FL involvement in the proximal jejunum, leading to a diagnosis of clinical stage I primary GI‐FL. The patient elected to undergo a watch‐and‐wait approach. Conclusion This case highlights the potential for colorectal‐FL lesions to be misidentified as adenomatous polyps, posing a diagnostic challenge.